2009
DOI: 10.1590/s1516-31802009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab for ocular neovascular diseases: a systematic review

Abstract: CONTEXT AND OBJECTIVE: Many eye diseases involve increased local levels of vascular endothelial growth factor (VEGF), and there are several therapeutic strategies for them. Thus, the aim of this study was to evaluate the effectiveness and safety of bevacizumab for treating eye diseases involving increased local levels of VEGF, as the assumed pathophysiological mechanism. DATA SOURCES:The following databases were systematically searched for evidence: PubMed, CENTRAL (Cochrane Library), Literatura Latino-America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…A recent systematic review [49] of bevacizumab in the treatment of ocular neovascular diseases identified 474 studies, of which nine were RCTs that employed the minimum methodological rigour necessary to generate robust data. Furthermore, methodological flaws within these trials, including potential performance bias in six of the studies and detection bias in five of the studies, precluded any definitive conclusions regarding the safety of intraocular bevacizumab administration.…”
Section: Important Considerations For Intraocular Bevacizumab Usementioning
confidence: 99%
“…A recent systematic review [49] of bevacizumab in the treatment of ocular neovascular diseases identified 474 studies, of which nine were RCTs that employed the minimum methodological rigour necessary to generate robust data. Furthermore, methodological flaws within these trials, including potential performance bias in six of the studies and detection bias in five of the studies, precluded any definitive conclusions regarding the safety of intraocular bevacizumab administration.…”
Section: Important Considerations For Intraocular Bevacizumab Usementioning
confidence: 99%
“…Review by Ziemssen et al .,[13] found off-label use of bevacizumab superior to PDT, in the short term, however the evidence was of moderate quality (2b level of evidence) primarily from before-after studies, case series and RCT's of bevacizumab for neovascular AMD. Andriolo et al .,[14] in their meta-analysis showed that BCVA was higher among those treated with bevacizumab than those in the PDT group (risk ratio, RR, 0.49; 95% confidence interval (CI), 0.31 to 0.78; P = 0.01). Jyothi et al ., summarized the findings from 5 RCT's and 50 observations studies that met “Strengthening the Reporting of Observational Studies in Epidemiology” (STROBE) criteria.…”
Section: Resultsmentioning
confidence: 99%
“…[1234567891011121314] With increasing life expectancy, the worldwide prevalence of AMD is set to increase. Neovascular AMD is characterized by abnormal growth of new blood vessels under the macula, it accounts for only 20% of the cases with AMD, but responsible for 90% of the cases of legal blindness.…”
mentioning
confidence: 99%
“…All these molecules bind to secreted VEGF and prevent its interaction with VEGF receptors. [13][14][15] Aflibercept is a recombinant fusion protein consisting of portions of VEGF receptors fused to Fc domain of IgG1. It acts as a soluble decoy receptor binding free VEGF.…”
Section: Introductionmentioning
confidence: 99%